Migration of sporozoites and merogony of Eimeria coecicola in gut-associated lymphoid tissue - Pakandl, M; Coudert, P; Licois, D (Parasitology research, 1993)
The invasive phase of Eimeria coecicola was studied during the first 80 h postinoculation (p.i.). Using a method that synchronized the life cycle, sporozoites were observed in the duodenum and the jejunum until 32 h p.i. They were seen first in the villous epithelial cells or in host cells resembling intraepithelial lymphocytes (IEL). Later they were observed in IEL in the lamina propria. After 48 h p.i., no coccidian stage was identifiable in the mucosa of the small intestine but sporozoites appeared in the lymphoid cells of lymphatic follicles of the gut-associated lymphoid tissue (vermiform appendix, sacculus rotundus, and Peyer's patches). The first merogony was observed 64 h p.i. in these lymphoid cells and in membranous epithelial cells (M-cells) but was never seen in the epithelium itself. Morphologically there were two types of meronts, depending on the host cell type, but in both cases the merozoites contained a refractile body and resembled sporozoites. The first meronts of the second generation were observed 80 h p.i. in the villous epithelial cells of the domes of the follicles of the gut-associated lymphoid tissue, where the further development of this Eimeria takes place. This pattern of invasion strongly suggests that sporozoites take an exclusively extraintestinal route to reach the target cells. Moreover, to our knowledge this is the first description of an eimerian merogony that does not take place in epithelial cells.
Keywords: Lymphoid Tissue; Peyer's Patches; lymfoidní tkáň; Animals; Cell Movement; Metamorphosis, Biological; Peyerovy pláty; apendix; zvířata; biologická proměna; pohyb buněk; Appendix; Intestines; kokcidióza; Eimeria; Coccidiosis; střeva